Identification of differentially expressed key genes of Longissimus lumborum samples from Portuguese Alentejano and Bísaro local pig breeds - Albuquerque, A. (2020)
Most of the swine industry nowadays is about productive and profitable fast-growing lean breeds raised under intensive conditions leading to meat and fat rich in saturated fatty acids. The Portuguese local Alentejano (AL) and Bísaro (BI) pig breeds present high intramuscular fat (IMF) content which contributes to highly appreciated pork products. These breeds have different ancestors: AL belongs to the Iberian group, presenting lower growth rates and higher lipid accretion and unsaturated fatty acids level when compared to BI, which belongs to the Celtic group, sharing ancestors with leaner breeds such as Large White and Landrace. The goal of this work was to compare the muscle gene expression profiles of AL and BI pig breeds to better understand the influence of the genetic background in the main metabolic processes occurring in the Longissimus lumborum (LL) muscle, namely in terms of lipid synthesis, muscle tissue formation, protein synthesis and cell proliferation. LL samples were obtained at slaughter, from adult AL and BI pigs with ~150kg body weight. Total RNA was extracted and sequenced for a transcriptome comparison analysis. A total of 250 genes were found to be differentially expressed (DE) in LL samples (q<0.05) conditional on breed, with 174 DE genes up-regulated in AL (log2(fold_change) = 0.65 to 7.03) and 76 in BI (log2(fold_change) = 0.63 to 4.53). Genes related to skeletal muscle development and function, such as MYH3, MYH13 or ACTN4, were significantly up-regulated in BI when compared to AL, which is in agreement with the higher muscle mass of the former breed. Genes involved in lipid metabolism were up-regulated in AL, including SCD (q=0.05), responsible for catalysing the reaction that introduces the first double bond into saturated fatty acyl-CoA substrates, which agrees with the higher unsaturation of fat tissues generally associated with the former breed. A functional enrichment analysis (metabolic pathways and GO enrichment) was performed for the DE genes and the identified functions included tissue development, cellular growth and proliferation, quantity of connective tissue and lipid metabolism. Potential regulators found that explain the observed gene expression changes in the dataset included molecules such as: ADORA2A, CEBPA, SMAD3 and PPARG (predicted to be activated in AL); HDAC and ASXL1 (predicted to be inhibited in AL).